Modelo de leilão de energia multiperíodo com representação linearizada da transmissão e da coordenação com o médio prazo para sistemas hidrotérmicos - Bregadioli, Gabriela Fernanda [UNESP] (2015)
The auction models traditionally used in energy markets for hydrothermal systems consist in single-period models. he formulation of these models usually does not represent the thermal constraints and network constraints, and it also does not consider the coordination between short and medium-term for hydrothermal generation. The representation of these features is made by ex post adjustments in order to ensure that the technical and operational limits of the generation and transmission systems are guaranteed. Such adjustments generate economic inefficiencies and cross-subsidies. The goal of this work is to propose a multiperiod auction for hydrothermal systems. This model incorporates the accurate representation of inter-temporal constraints and network constraints, and it also considers the coordination between short and medium-term schedulings in order to ensure the lower thermal complementation in the present and in the future. Three coordinating approaches between the short and medium term schedulings are presented: primal, dual and primal-dual coordination. For the validation of the auction model proposed in this work, computational tests are carried out with the IEEE 24 bus RTS-1996 system, for a base case, which does not consider the cordination between short and medium-term schedulings, and later for the cases that include the coordination in the medium-term scheduling